PARENT AND TEACHER CHALLENGES IN NAVIGATING THE DIGITAL ERA - Trisnawaty Trisnawaty; Fatimah HS; Syarifuddin Ondeng; Syahruddin Usman (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2025)
The rapid advancement of digital technology in the era of Industrial Revolution 4.0 and Society 5.0 has fundamentally transformed the way families and schools’ function in educating children. Parents and teachers are increasingly confronted with complex challenges in guiding children amidst the influx of information, digital content, and internet-based learning. This article aims to analyze the roles of parents and teachers in responding to digital challenges, particularly in the context of Islamic education. Employing a qualitative approach through library research, the study synthesizes findings from academic literature, national surveys, and recent statistical data (2015–2024). The discussion is framed by Bronfenbrenner's Ecological Systems Theory and the Islamic framework of Maqāṣid al-Sharīʿah. Findings indicate a significant gap in digital literacy among parents and teachers, limited institutional readiness for digital pedagogy, and increasing exposure of children to harmful digital content. The article argues that current research often isolates the roles of parents and teachers, overlooking their synergistic potential in shaping children's character through a values-based framework. As a novelty, this study proposes a four-pillar tarbiyah model—parents, teachers, community, and the state—rooted in Islamic principles to promote digital ethics, character education, and spiritual development. This integrative approach is expected to serve as a practical and conceptual guide in constructing a holistic digital education ecosystem that aligns with Islamic values.